Etiology of Minor Troponin Elevations in Patients with Atrial Fibrillation at Emergency Department-Tropo-AF Study - Samuli Jaakkola; Tuomas Paana; Ilpo Nuotio; Tuomas O. Kiviniemi; Jussi-Pekka Pouru; Pekka Porela; Fausto Biancari; K. E. Juhani Airaksinen (MDPI, 2025)
Patients with atrial fibrillation (AF) presenting to the emergency department (ED) often have elevated cardiac troponin T (TnT) levels without evidence of type 1 myocardial infarction. We sought to explore the causes and significance of minor TnT elevations in patients with AF at the ED. All patients with AF admitted to the ED of Turku University Hospital between 1 March, 2013 and 11 April, 2016, and at least two TnT measurements, were screened. Overall, 2911 patients with a maximum TnT of 100 ng/L during hospitalization were analyzed. TnT was between 15 and 100 ng/L in 2116 patients. The most common primary discharge diagnoses in this group were AF (18.1%), infection (18.3%), ischemic stroke/transient ischemic attack (10.7%), and heart failure (5.0%). Acute coronary syndrome (ACS) was equally uncommon both in patients with normal TnT and elevated TnT (4.4% vs. 4.5%). Age >= 75 years, low estimated glomerular filtration rate (eGFR), high C-reactive protein (CRP), and hemoglobin <10.0 g/dL, were the most important predictors of elevated TnT. Importantly, TnT elevation was a very frequent (>93%) finding in elderly (>= 75 years) AF patients with either low eGFR or high CRP. In conclusion, minor TnT elevations carry limited diagnostic value in elderly AF patients with comorbidities.